Determinant Factors of Maxillary Arch Dimension of Students Aged 18 - 25 Years at Prosthetic Department Bhittai Dental and Medical College - Jawaid Sultan, Faryal Manzoor, Umar Khayyam, Shuja Hamid, Samreen Zubair, Tabinda Hanif, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the factors of maxillary arch dimension of students aged 18–25 years in the prosthetic department at Bhittai Dental and Medical College Methods: This cross-sectional study was done at the prosthetic department at Bhittai Dental and Medical College, MirpurKhas. All the students having Class I canine and molar relationships; well-aligned upper and lower dental arches; mixed dentition; good facial symmetry; and no previous orthodontic treatment. Dental arch dimensions of width, length, and depth were taken by one examiner using the Korkhaus’ compass and a digital pachymeter. All the data was collected by the study proforma and SPSS version 26 was used for the purpose of analysis. Results: A total of 50 students were studied. Their mean age was 22.68+3.32 years. According to the arch width, the mean inter canine distance was 35.28+1.98 mm, the mean inter pre molar distance was 42.92+2.36 mm, the mean inter first molar distance was 52.48+4.03 mm, and the mean inter 2nd molar distance was 59.52+3.61mm. According to the maxillary arch length, the anterior arch length was 8.32+1.34mm, molar ventricle distance was 29.72+2.52 mm and the total arch length was 43.2+2.1mm. In the arch width and length, the mean inter 2nd molar distance and anterior arch length were statistically insignificant according to age and gender (p-<0.05). Conclusion: In conclusion, within the age range that was investigated, slight gender discrepancies were evident using all available approaches in maxillary arch width and length. There was found a slight difference in age groups and gender as the average maxillary arch width and length were observed to be slightly higher than females. Keywords: Maxillary arch, width, length, age, gender